Autophagy-independent function of Atg8 in lipid droplet dynamics in yeast. (16th December 2016) - Maeda, Yuichiro; Oku, Masahide; Sakai, Yasuyoshi
Abstract : Dynamic features of lipid droplets include growth and degradation of the organelle. Autophagy, a system for the transport of cytoplasmic components to be degraded into the lysosome/vacuole, is regarded to be responsible for the degradation of lipid droplets. Atg8 protein in the yeast Saccharomyces cerevisiae is recruited to membrane structures synthesized during autophagy via a lipidation process. In this study, we report a novel function of Atg8 in lipid droplet dynamics. We found that loss of Atg8 specifically resulted in a decrease in the quantity of lipid droplets in cells at stationary phase. This protein was detected in a lipid droplet fraction independent of its lipidation. Loss of Atg8 hemifusion activity also caused a decrease in the quantity of lipid droplets. Consistent with these results, isolated lipid droplets underwent assembly into large clusters when incubated with Atg8 possessing hemifusion activity. The loss of Atg8 did not reduce the quantity of lipid droplets in a mutant defective in lipolysis, another system for lipid droplet degradation, which strongly suggests the function of Atg8 in antagonizing lipolysis. Together these results indicate a specific function of Atg8 in maintaining the quantity of lipid droplets that is independent of its autophagic function.